Numerical investigation of blade tip with different groove effect and its dynamic analysis of axial flow fan. Issue 15 (18th November 2021) - Vala, Jignesh; Patel, D.K.; Panchal, Hitesh
Abstract : In turbomachinery field, axial flow fan is the most important component of the rotatory system as it increases the pressure rise and improves fan characteristic. The performance of axial fan with different grooved blade tips simulated using commercial solver. This effect of the various grooved blade on total pressure ratio, noise characteristic, stress deformation, analysis of dynamic characteristics as well as flow distribution are investigated.